2000
DOI: 10.1099/00221287-146-10-2679
|View full text |Cite
|
Sign up to set email alerts
|

Dioctyl phthalate increases the percentage of unsaturated fatty acids with a concomitant decrease in cellular heat shock sensitivity in the yeast Saccharomyces cerevisiae

Abstract: In the past it has been reproducibly demonstrated that 37 SC-grown DBY747 yeast cells have 29 % more unsaturated fatty acids and a 3 SC higher maximal heat shock response (HSR) than their 25 SC counterparts. Suddenly the HSR and lipid profiles of cells grown at 25 SC and 37 SC became indistinguishable from one another. This paper reports an aberrantly high level of unsaturated fatty acids and an abnormally insensitive HSR in cells grown at 25 SC in yeast nitrogen base (YNB) that has been reconstituted from deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Cell survival falls dramatically to 20% at 45 °C, at which temperature the induction of the HS reporter gene is minimal and DCF fluorescence begins to increase again (see Figure 2A, B). Previous work from this laboratory provided evidence of membrane involvement in the HSR (Curran and Khalawan, 1994) and demonstrated that HS sensitivity is tightly correlated with the level of unsaturated fatty acids in the yeast cell (Chatterjee et al , 1997; Curran et al , 2000). Future work will examine therefore whether lipid hydroperoxides (LOOHs), a specific class of ROS, may also be effectors of the HSR and/or be considered as part of the defence mechanism against oxidative damage to other cell components.…”
Section: Discussionmentioning
confidence: 97%
“…Cell survival falls dramatically to 20% at 45 °C, at which temperature the induction of the HS reporter gene is minimal and DCF fluorescence begins to increase again (see Figure 2A, B). Previous work from this laboratory provided evidence of membrane involvement in the HSR (Curran and Khalawan, 1994) and demonstrated that HS sensitivity is tightly correlated with the level of unsaturated fatty acids in the yeast cell (Chatterjee et al , 1997; Curran et al , 2000). Future work will examine therefore whether lipid hydroperoxides (LOOHs), a specific class of ROS, may also be effectors of the HSR and/or be considered as part of the defence mechanism against oxidative damage to other cell components.…”
Section: Discussionmentioning
confidence: 97%
“…Carratu et al (1996) proposed that membrane composition, and more precisely the ratio of saturated to unsaturated fatty acids might be involved in the transduction of a signal that induces transcription of HSP genes. Other works have shown that plasma membrane lipids affect the response to heat stress (Chatterjee et al, 1997;Curran et al, 2000). Recently, Gervais et al (2003) proposed a possible scenario for the cellular response of cell to heat shock, which involves an increase in membrane fluidity leading to an increase in cellular volume.…”
Section: Introductionmentioning
confidence: 99%
“…Carratu et al (1996) propuseram que a composição da membrana, mais precisamente o padrão de saturação e insaturação dos seus ácidos graxos, pode apresentar envolvimento com a resposta das células ao choque térmico. Outros autores também demonstraram que a composição lipídica da membrana plasmática afeta a resposta da levedura ao estresse térmico (CHATTERJEE; CURRAN, 1997;CURRAN et al, 2000).…”
Section: Introductionunclassified